Concurrency coverage criteria for activity diagrams - Mahesh Shirole; Rajeev Kumar (IET Software)
Abstract Existing coverage criteria for Unified Modeling Language (UML)‐based system design have used mostly structural constructs and sequential‐behavioural coverage criteria. However, concurrent‐behavioural coverage criteria are not sufficiently explored. The basic path coverage criteria, in UML‐based system design, do not distinguish between non‐interleaving and interleaving execution paths in concurrent activity diagrams. Herein, the main contribution is to present a new set of coverage criteria, based on activity‐interleaving paths for concurrent activity diagrams. For this, first, we modified the definitions of basic path and basic path coverage criterion, and then we defined the interleaving activity path, interleaving activity path coverage, and total activity path coverage criteria. It is observed that the proposed coverage criteria explore most of the concurrency behaviours to uncover concurrency errors. They help to uncover different types of concurrency errors like synchronization, data‐race, and deadlock.